Cooler rooms on a hotter planet? Household coping strategies, climate change, and air conditioning usage in rural China. (October 2020) - Zhang, Xiao-Bing; Sun, Jiayu; Fei, Yinxin; Wei, Chu
Abstract: Ownership and usage of air conditioners (AC) have increased dramatically in the past few decades as global warming and the increasing occurrence of extreme hot weather have become major concerns. However, there is a lack of household-level studies on the effect of climate change on AC energy consumption and usage patterns, especially for developing countries, which have great potential for AC adoption and usage. This study employed data from the Chinese Residential Energy Consumption Survey, matched with weather data, to analyze the effect of climate change on AC usage at the household level by using AC energy consumption and usage time as AC usage indicators. The result shows that cooling degree days significantly influence both AC energy consumption and AC usage time, while the average relative humidity affects only AC usage time. In addition, we find that other socio-economic variables, including dwelling age, occupation, and dwelling size, also influence AC usage.